Integrable Couplings of the Boiti-Pempinelli-Tu Hierarchy and Their Hamiltonian Structures (Advances in Applied Mathematics and Mechanics, 2018)
Integrable couplings of the Boiti-Pempinelli-Tu hierarchy are constructedby a class of non-semisimple block matrix loop algebras. Further, through using thevariational identity theory, the Hamiltonian structures of those integrable couplingsare obtained. The method can be applied to obtain other integrable hierarchies.